Perlakuan Akuntansi Pembiayaan Gadai dan Cicil Emas PT Bank Syariah Mandiri Jember - Neni Maulina Rahman; S. Sudarno; Ahmad Roziq (UPT Penerbitan Universitas Jember, 2018)
This study aims to identify how determine how for mortgage financing in gold and credit gold in PT Bank Syariah branch office Jember .data collection techniques in this research is the primary data with interviews and Secondary Data From Notes or archives relating to the accounting treatment financing gold and credit Gold. The analysis used in this research is using descriptive qualitative comparative analisiss by comparing the application of the accounting treatment of mortgage financing syariah gold and credit gold with PSAK 107 and PSAK 102. The results of this study indicate that accounting treatment which includes the recognition, measurement, presentation, disclosure mortgage financing syaria gold and credit gold have with PSAK 107Accounting for Ijarah and PSAK 102, Accounting for Murrabahah.Keywords: Pawn gold financing, Gold credit financing, PSAK No 107, PSAK No 102